P84Pathway dissection in cardiac muscle cell death: MAP4K4 as a therapeutic target. (15th July 2014) - Fiedler, LR; Chapman, K; Maifoshie, E; Sampson, R; Low, C; Traulau-Steward, C; Schneider, MD
Abstract: Cell death has been shown to be causative in progression to heart failure. However, no established pharmacological treatments directly address this problem in either acute or chronic settings. We previously identified MAP4K4/HGK as an activator of the TAK1 - JNK pathway in cardiac cell death, whose inhibition by dominant-negative mutations or shRNA knockdown confers protection in cultured rat neonatal cardiomyocytes. Confirming the relevance of MAP4K4 in a human setting, shRNAmir-mediated knockdown was protective against H202-induced cardiomyocyte cell death in human iPSC-derived cardiomyocytes. To address this therapeutic potential, we initiated a small molecule discovery programme. Screening of known kinase inhibitors for activity against recombinant MAP4K4 kinase domain identified four with a pIC50 > 7 (series 1). To generate novel compounds, features of similar charge distribution were analysed by pharmacophore field-point modeling and used to generate a consensus pharmacophore model for inhibition of MAP4K4. This model was then used to interrogate 2.5M structures in silico. The top 40 ranked compounds were synthesized and tested for activity against MAP4K4 and the most potent from each of two chemical series (series 2) taken forward. Series 2 had much improved selectivity (3-5 of 141 kinases inhibited > 50% at 1 μM) over series 1, and further, was more selective and equally potent (IC35-100 nM) as two small molecule inhibitors described by Pfizer. In addition, series 2 were not toxic to cardiomyocytes up to 10 μM, while those described by Pfizer, and two of series 1, were toxic (measured by hypodiploid DNA content, Caspase 3 activation and ATP production). Importantly, both compounds from series 2 showed protection against H202- or C2-ceramide mediated cell death in rat neonatal cardiomyocytes (measured by hypodiploid DNA content). Thus we have obtained promising lead compounds for optimization and experimental studies, and shown that inhibition of MAP4K4 in vitro, whether by knockdown of expression or pharmacological inhibition, is protective against cell death in cardiomyocytes.